Biology at Work : Rethinking Sexual Equality - Browne, Kingsley (Book collections on Project MUSE., 2002)
Biology at Work brings an evolutionary perspective to bear on issues of women in the workplace: the "glass ceiling," the "gender gap" in pay, sexual harassment, and occupational segregation. While acknowledging the role of discrimination and sexist socialization, Browne suggests that until we factor real biological differences between men and women into the equation, the explanation remains incomplete. Browne looks at behavioral differences between men and women as products of different evolutionary pressures facing them throughout human history.